Aging Alters Daily and Regional Calretinin Neuronal Expression in the Rat Non-image Forming Visual Thalamus - Fiuza, Felipe P.; Queiroz, José Pablo G.; Aquino, Antônio Carlos Q.; Câmara, Diego A.; Brandão, Luiz Eduardo M.; Lima, Ramon H.; Cavalcanti, José Rodolfo L. P.; Engelberth, Rovena Clara G. J.; Cavalcante, Jeferson S. (Frontiers in Aging Neuroscience, 2021)
Aging affects the overall physiology, including the image-forming and non-image forming visual systems. Among the components of the latter, the thalamic retinorecipient intergeniculate leaflet and ventral lateral geniculate nucleus conveys light information to subcortical regions, adjusting visuomotor and circadian functions. It is noteworthy that several visual related cells, suchlike neuronal subpopulations in the IGL and vLGN, are neurochemically characterized by the presence of calcium binding proteins. Calretinin (CR), a representative of such proteins, denotes region-specificity in a temporal manner by variable day-night expression. In parallel, age-related brain dysfunction and neurodegeneration are associated with abnormal intracellular concentrations of calcium. Here, we investigated whether daily changes in the number of CR neurons are a feature of the aged IGL and vLGN in rats. To this end, we perfused rats, ranging from 3 to 23 months of age, within distinct phases of the day, namely zeitgeber times (ZTs). Then, we evaluated CR immunolabeling through design-based stereological cell estimation. We observed distinct daily rhythms of CR expression in the IGL and in both the retinorecipient (vLGNe) and non-retinorecipient (vLGNi) portions of the vLGN. In the ZT 6, middle of the light phase, CR cells are reduced with aging in the IGL and vLGNe. In the ZT 12, transition between light to dark, an age-related CR loss was found in all nuclei. While CR expression predominates in specific spatial domains of vLGN, age-related changes appears not to be restricted at particular portions. No alterations were found in the dark/light transition or in the middle of the dark phase, ZTs 0 and 18 respectively. These results are relevant in the understanding of how aging shifts the phenotype of visual related cells at topographically organized channels of visuomotor and circadian processing.